2016
DOI: 10.1111/1753-0407.12500
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into knowledge, attitude, and practice regarding medical nutrition therapy among patients with diabetes in China: Results from a national multicenter cross‐sectional study

Abstract: Patients with diabetes and prediabetes achieved moderate scores for KAP towards MNT. Glycemic control was positively correlated with the KAP score. Thus, MNT education should be improved, with a particular focus on feasibility and authenticity and professionalism, in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The findings indicate that many patients perceived diabetes as an ambiguous illness that they did not understand well. This result is consistent with previous research showing that the majority of Chinese T2D patients have a low level of diabetes‐related knowledge (Jing et al, ). This suggests that diabetes health education (with high feasibility, authenticity, and professionalism) is essential and urgently required in China.…”
Section: Discussionsupporting
confidence: 93%
“…The findings indicate that many patients perceived diabetes as an ambiguous illness that they did not understand well. This result is consistent with previous research showing that the majority of Chinese T2D patients have a low level of diabetes‐related knowledge (Jing et al, ). This suggests that diabetes health education (with high feasibility, authenticity, and professionalism) is essential and urgently required in China.…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that other more acceptable types of exercise, such as yoga and tai chi, could be take into consideration, but more evidence is needed to support their effectiveness (Colberg et al, 2016). Our results also confirm that there is a huge gap in the current practice of medical nutrition therapy (Jing et al, 2017). The authenticity and professionalism of the medical nutrition therapy need to be improved.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the participants acknowledged the importance of some education on the role of nutrition and physical activity levels in diabetes management, especially for people who had been recently diagnosed or lacked knowledge, before accessing the platform. This seems fruitful because knowledge, attitude, and practice seem to be positively related to glycemic control [ 52 ]. Although studies have suggested that education is an important aspect to improve existing mHealth apps in diabetes management, this has only been adopted by a few apps [ 15 , 47 ].…”
Section: Discussionmentioning
confidence: 99%